2016
DOI: 10.1016/j.repc.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Associação positiva entre razão cintura‐estatura e presença de hipertensão em adolescentes

Abstract: A positive association was found between WHR and the presence of hypertension in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Several studies have demonstrated that individuals with the same WC but different heights are unlikely to have the same cardiometabolic risks [ 10 ]. The early detection of hypertension is crucial for its control and prevention, in adults; however, since BP is not routinely tested in most adolescents, it is difficult to monitor the condition in them [ 11 , 25 ]. Recently, the WHtR was shown to be the most important predictor of BP and hypertension, in Saudi Arabian adult populations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that individuals with the same WC but different heights are unlikely to have the same cardiometabolic risks [ 10 ]. The early detection of hypertension is crucial for its control and prevention, in adults; however, since BP is not routinely tested in most adolescents, it is difficult to monitor the condition in them [ 11 , 25 ]. Recently, the WHtR was shown to be the most important predictor of BP and hypertension, in Saudi Arabian adult populations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…WHtR is a simple and practical tool used for the measurement of metabolic risk factors [ 1 , 10 , 11 ]. A systematic review inferred that WHtR may be beneficial, regardless of the age-, gender-, and ethnicity-specific values [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding abdominal adiposity, in this study 4.2% of the study sample presented enlarged values, whereas 95.8% presented eutrophic values. Th e opposite prevalence was found in a research carried out with 1030 adolescents in the countryside of the state of Rio Grande do Sul (Southern Brazil), which identifi ed abdominal obesity in 24% of adolescents; (20) and a study carried out in Fortaleza, state of Ceará (Northeastern Brazil), with 702 students, which showed a prevalence of enlarged WC in 13.6% of participants. (24) Considering NC levels, it was observed that 30% of the sample present inadequate parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, studies carried out with this public to investigate risk factors and/or excessive weight, as well as other studies that investigated community health/illness situation, portrayed that the female sex was the most frequent one. (20) Regarding the distribution of clinical variable among adolescents, it was noticed that 18.5% of adolescents presented excessive weight (overweight/ obesity) when assessed for BMI, split between 12.9% overweight and 5.6% obese. Th is is a higher result than the one in a study carried out with 305 adolescents in Petrolina, state of Pernambuco, which showed excessive weight in 16% of students.…”
Section: Discussionmentioning
confidence: 99%